2017
DOI: 10.1128/jvi.01836-16
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenesis of Dengue Virus Protein NS2A Revealed a Novel Domain Responsible for Virus-Induced Cytopathic Effect and Interactions between NS2A and NS2B Transmembrane Segments

Abstract: The NS2A protein of dengue virus (DENV) has eight predicted transmembrane segments (pTMS1 to -8) and participates in RNA replication, virion assembly, and host antiviral response. However, the roles of specific amino acid residues within the pTMS regions of NS2A during the viral life cycle are not clear. Here, we explore the function of DENV NS2A by introducing a series of alanine substitutions into the N-terminal half (pTMS1 to -4) of the protein in the context of a DENV infectious clone or subgenomic replico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 37 publications
0
26
1
Order By: Relevance
“…Moreover, scanning mutagenesis studies of NS2A implicated that the intermolecular interactions between pTMSs are critical in a DENV life cycle (25,33). Mutations of multiple conserved residues in different pTMSs, which are located inside or outside the ER lumen or within the ER membrane, showed different defect patterns (25,33). K135 of NS2A is predicted to locate in pTMS5 at the lumen side of ER (30), which possibly involves NS2A VSR function by mediating pTMS interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, scanning mutagenesis studies of NS2A implicated that the intermolecular interactions between pTMSs are critical in a DENV life cycle (25,33). Mutations of multiple conserved residues in different pTMSs, which are located inside or outside the ER lumen or within the ER membrane, showed different defect patterns (25,33). K135 of NS2A is predicted to locate in pTMS5 at the lumen side of ER (30), which possibly involves NS2A VSR function by mediating pTMS interactions.…”
Section: Discussionmentioning
confidence: 99%
“…It is also reported that the N-terminal half of NS2a protein of dengue virus 2 is implicated in causing cytopathic effect (CPE) due to virus, whereas the C-terminal portion takes part in assembly of virus particle and subsequent secretion from the cell. This fact can be exploited for development of vaccines and drugs against dengue infection ( 46 ). NS2b is a 14 kDa membrane-associated protein.…”
Section: Dengue Virus Proteinsmentioning
confidence: 99%
“…The flavivirus nonstructural protein NS2A is a nonenzymatic, integral membrane protein (20). In addition to playing an important role in viral RNA replication (21), NS2A also performs an essential role in virus assembly (3,(22)(23)(24). Previous studies revealed that NS2A interacts with NS2B in mammalian cells (12,13,24).…”
Section: Fig 10mentioning
confidence: 99%